Apparent Competition, Lion Predation, and Managed Livestock Grazing: Can Conservation Value Be Enhanced? - Ng'weno, Caroline C.; Buskirk, Steven W.; Georgiadis, Nicholas J.; Gituku, Benard C.; Kibungei, Alfred K.; Porensky, Lauren M.; Rubenstein, Daniel I.; Goheen, Jacob R. (Frontiers in Ecology and Evolution, 2019)
Predator restorations often result in apparent competition, where co-occurring prey populations experience asymmetric predation pressure driven by predator preferences. In many rangeland ecosystems, livestock share the landscape with wildlife, including ungulates and the large carnivores that consume them. We examined whether apparent competition reorganized prey communities following restoration of lions (Panthera leo) to a savanna ecosystem, and whether and how livestock management could alter this indirect interaction between lions and their prey. Three lines of evidence supported the hypothesis that Jackson’s hartebeest (Alcelaphus bucelaphus lelwel; an ungulate of conservation concern) are suppressed via lion-mediated apparent competition. First, hartebeest exhibited an Allee effect where they were exposed to lions, but displayed negative density-dependent population growth where they were protected from lions. Second, spatial overlap between plains zebra (Equus burchelli; the primary prey of lions) and hartebeest further exacerbated lion predation on hartebeest. Finally, hartebeest were killed selectively by lions, whereas zebra were killed by lions in proportion to their abundance. We then tested whether glades (nutrient-rich hotspots created by abandoned cattle [Bos indicus] corrals) could be used to manipulate top-down control of hartebeest via their influence on the spatial distribution of zebra. Zebra aggregated at glades, and survival of hartebeest increased with increasing distance from glades, suggesting that corrals may be placed on the landscape away from hartebeest to create spatial refuges from lions. Our findings demonstrate how informed placement of livestock corrals can be used to manipulate the spatial distribution of primary prey (zebra), thereby reducing apparent competition suffered by hartebeest. Our work further provides an example of how integrating apparent competition theory with proactive livestock management can improve conservation efforts in multiple-use landscapes.